Haar wavelet collocation method for solving stagnation point flow over a nonlinearly stretching/shrinking sheet in a carbon nanotube with slip effect - Hasanah, N. S.; Rasedee, A. F. N.; Bachok, N.; Wong, T. J.; Hasan, M. (Lviv Polytechnic National University., 2023)
This paper investigates the influence of slip effect on a stagnation point flow towards a shrinking/stretching sheet in carbon nanotube. The governing system of the partial differential equation is converted into a set of nonlinear ordinary differential equations by using a similarity transformation. The nonlinear ordinary differential equations are then solved numerically by Haar wavelets collocation method. The influence of the various parameters on the characteristics of the fluid flow and heat transfer is analyzed. Results are presented in terms of the skin friction coefficient and local Nusselt number, whereas the velocity and temperature profiles in the form of figures and thus, discussed in details